2015
DOI: 10.3109/10837450.2015.1045617
|View full text |Cite
|
Sign up to set email alerts
|

Development of a bone targeted thermosensitive liposomal doxorubicin formulation based on a bisphosphonate modified non-ionic surfactant

Abstract: Bone is among the most common sites of metastasis in cancer patients, so it is an urgent need to develop drug delivery systems targeting tumor bone metastasis with the feature of controlled release. This study aimed to delivery of thermosensitive liposomal doxorubicin to bone for tumor metastasis treatment. First, Brij78 (polyoxyethylene stearyl ether) was conjugated with Pamidronate (Pa). By incorporating Pa-Brij78 to DPPC/Chol liposomes, we developed Pa surface functionalized liposomes. The Pa-Brij78/DPPC/Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Liposome can be prepared in different sizes ranging from 50 nm to more than 1000 nm, depending on the composition of phospholipid and cholesterol molecules used. The presences of phospholipid layers make liposome an ideal carrier to encapsulate water insoluble drugs especially most chemotherapeutic drugs such as paclitaxel and doxorubicin [39,47,48]. Paclitaxel liposome consisting of dilauroylphosphatidylcholine (DLPC) at drug-tolipid ratio of 1:10 (w/w) were prepared in butanol and lyophilized to prepare a DPI formulation.…”
Section: Liposomesmentioning
confidence: 99%
“…Liposome can be prepared in different sizes ranging from 50 nm to more than 1000 nm, depending on the composition of phospholipid and cholesterol molecules used. The presences of phospholipid layers make liposome an ideal carrier to encapsulate water insoluble drugs especially most chemotherapeutic drugs such as paclitaxel and doxorubicin [39,47,48]. Paclitaxel liposome consisting of dilauroylphosphatidylcholine (DLPC) at drug-tolipid ratio of 1:10 (w/w) were prepared in butanol and lyophilized to prepare a DPI formulation.…”
Section: Liposomesmentioning
confidence: 99%
“…So, targeted delivery of chemotherapeutic with BP‐conjugated thermo‐sensitive liposomes seems a good therapeutic opportunity. To this end, Song et al designed thermo‐sensitive liposomes containing doxorubicin and conjugated them with pamidronate 213 . As expected the pamidronate conjugated liposomes exhibited stronger binding affinity to HA compared to nonconjugated ones.…”
Section: Targeted Drug Delivery Systemsmentioning
confidence: 93%
“…As expected the pamidronate conjugated liposomes exhibited stronger binding affinity to HA compared to nonconjugated ones. They also showed that doxorubicin was completely released when liposomes were heated up to 42°C either alone or in combination with HA 213 …”
Section: Targeted Drug Delivery Systemsmentioning
confidence: 98%
“…Similarly, Song et al 61 introduced Brij78 (polyoxyethylene stearyl ether) and pamidronate (Pa)-conjugated PA-Brij78 into DPPC/Chol liposomes to prepare PA surface functional liposomes. The in vitro binding of PB liposomes embedded with adriamycin to hyaluronic acid (HA), the temperature-dependent release of doxorubicin and the cytotoxicity were studied.…”
Section: Liposomesmentioning
confidence: 99%